2018
DOI: 10.9767/bcrec.14.1.2548.17-27
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic of Adsorption Process of Sulfonated Carbon-derived from Eichhornia crassipes in the Adsorption of Methylene Blue Dye from Aqueous Solution

Abstract: The evaluation of kinetic adsorption process of sulfonated carbon-derived from Eichhornia crassipes in the adsorption of methylene blue dye from aqueous solution has been carried out. The sulfonated carbon-derived from E. crassipes (EGS-600) was prepared by carbonation of E. crassipes powder at 600 °C for 1 h, followed by sulfonation with concentrated sulfuric acid for 3 h. The physical properties of the adsorbents were characterized by using Fourier transform infrared spectroscopy, X-ray diffraction (XRD), sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…[Riza et al, 2020; Jedynak et al, 2021; Zaghoul et al, 2021], but in the case of ΔH, it is only reported for nanoparticles, mesopore carbons and hydrogel [Anastopoulos et al, 2017; Jedynak et al, 2021; Riza et al, 2020] they have an endothermic nature for MB and MO, respectively, which in the obteined results are consistent with WLN.In other studies, it was determined that there is an exothermic process where modified hydroxyapatites are used as adsorbents[Guan et al, 2018], biochar from E. crassipes[Nurhadi et al, 2019], chitosan/cellulose[Xu et al, 2021], biochar with pineapple leaves[Soltani et al, 2021)] and MgAl[Zaghoul et al, 2021] this behavior is what was determined for the WLW adsorbent. In the case of the randomness of the solid/liquid interface in the…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…[Riza et al, 2020; Jedynak et al, 2021; Zaghoul et al, 2021], but in the case of ΔH, it is only reported for nanoparticles, mesopore carbons and hydrogel [Anastopoulos et al, 2017; Jedynak et al, 2021; Riza et al, 2020] they have an endothermic nature for MB and MO, respectively, which in the obteined results are consistent with WLN.In other studies, it was determined that there is an exothermic process where modified hydroxyapatites are used as adsorbents[Guan et al, 2018], biochar from E. crassipes[Nurhadi et al, 2019], chitosan/cellulose[Xu et al, 2021], biochar with pineapple leaves[Soltani et al, 2021)] and MgAl[Zaghoul et al, 2021] this behavior is what was determined for the WLW adsorbent. In the case of the randomness of the solid/liquid interface in the…”
mentioning
confidence: 58%
“…This behavior was observed using mesoporous activated carbon [Azam et al, 2020] for the adsorption of MB and MO, it was found that the adsorption capacity decreases with the increase of Cads, causing an increase in the removal of dyes (98.5% for MO and 82% for MB). Moreover, the use of biochar from natural sources such as black sapote leaves [Herrera-González et al, 2019], E. crassipes [Nurhadi et al, 2019], Spirulina algae residues [Zhu et al, 2021], chestnut hull [Zhang et al, 2018] lychee seeds, banana peel [Srivatsav et al, 2020] obtaining in these works a removal percentage of 66.7 up to 99.9% for both dyes.…”
Section: Thermodynamic Analysis Of the Of Mb And Mo Adsorption Processmentioning
confidence: 99%
“…The sulfonation process follows the previous research [23]. Every gram carbon was mixed with 6 mL sulfuric acid (98%, JT Baker) and stirred at room temperature for 3 h. The acid remaining in the sample was washed with distilled water and dried in an oven at 110 °C for overnight.…”
Section: Sulfonation Processmentioning
confidence: 99%
“…Hence, TiO2 is further modified with carbon source via sulfonation to enhance the adsorption capability. The function of sulfonation process was to enhance the number of oxygen functional groups that can serve as the adsorption sites, while increasing hydrophilicity [23]. The oxygen functional groups onto sulfonated carbon from E. crassipes act an importable in uniformly dispersing TiO2 on the surface and tailoring the particle size of TiO2, which result in great enhancement of adsorption capacity of dyes due to higher surface area.…”
Section: Introductionmentioning
confidence: 99%
“…Different adsorbents have been synthesized for the removal of dyes from clays such as SBA-15, Bentonite, and other materials [ 2 , 4 , 17 , 27 , 28 , 29 ], up to the manufacture of activated carbon from different sources, however, there are large losses and high operating costs due to the possibility of pore blockage, hydroscoping, and incineration when using high temperatures [ 5 , 19 , 22 , 24 , 27 , 28 , 29 ]. These drawbacks have encouraged several researchers to study other cheap, abundant materials that have similar efficiency to materials synthesized by chemical processes, therefore the use of agro-industrial residues was considered, which are cheap and, easily available materials that only need a simple pretreatment and are materials with properties that can be exploited in another industry as well as being good candidates for the adsorption of various contaminants [ 8 , 12 , 14 , 19 , 22 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. These materials are mainly constituted by lignocellulosic groups, peels of various fruits and vegetables furthermore, these materials have been used as adsorbents of various dyes including PR and GV with good results [ 4 , 5 , 11 , 12 , 13 , 18 , 22 , 23 , 24 , 25 , 26 , 33 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%